Influence of the Climate Policy of the European Union on the Competitiveness of Pollution-generating Sectors of the Polish Economy in the Context of Sustainable Development - Burchard-Dziubińska, Małgorzata (Comparative Economic Research. Central and Eastern Europe, 2012)
The text analyses the influence of the EU climate policy on the competitiveness pollution-generating of sectors of the Polish economy. Study of literature and the results of the questionnaire survey, carried out in 2008 in enterprises located in Poland and representing the steel, glass, aluminium and cement industries became a basis for formulating conclusions concerning the consequences of the climate policy already implemented and planned after 2012. The EU climate policy, particularly the common system of emission allowances trade, makes the enterprises face new developmental barriers. The expected increase in production costs will not only slow down the production dynamics, but may also entail lowering the competitiveness of Polish companies compared to companies from outside the EU, to which the greenhouse gasses emission limits do not apply. Adverse consequences for employment and for regional development should also be considered indisputable. If that was accompanied by an emission leakage outside the EU, achieving the global purposes of the climate policy would also become questionable. The businesses surveyed represent industries which are pollution generators by their nature and even ecologically-oriented technological progress is incapable of ensuring considerable emission reductions without general switching of the economy to renewable energy sources.